Length-Weight Relationships of two Clupeonella species (Clupeidae) from Northwestern Turkey - Kemal Aydoğan; Müfit Özuluğ (Turkish Journal of Bioscience and Collections, 2020)
The length-weight relationships (LWRs) of Clupeonella cultriventris and Clupeonella muhlisi were analysed. Fish samples were collected gill nets (10 mm mesh sized) from the Büyükçekmece Reservoir and Küçükçekmece Lagoon April and June 2016. Samples from Durusu Reservoir and Uluabat Lake were obtained from Istanbul University Science Faculty Hydrobiology Museum. The values of parameter b in the LWR equations varied from 3.177 (Küçükçekmece Lake population) to 3.496 (Büyükçekmece Reservoir population) for C. cultriventris and 3.258 (Uluabat Lake) for C. muhlisi.